PERBEDAAN PENDAPATAN NELAYAN BAGAN TANCAP BERDASARKAN JARAK BAGAN DARI PANTAI DI DESA MUARA BADAK ILIR KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Suwartono Mujiono; Muhammad Syafril; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2015)
The research aims to find out the comparison of fishermen incomes using stationary lift net and operating them inshore and offshore and to find out the factors affecting to the incomes of the stationary lift net fishermen in Muara Badak Ilir. The research was conducted from December 2013 to May 2014, in the research location of Muara Badak Ilir Village, Muara Badak Sub-district, Kutai Kartanegara District. The sample consisted of 30 fishermen taken by using disproportionate stratified random sampling method. The data were collected using direct observation and interview to the respondents. The results of research showed that the difference of average incomes between inshore and offshore stationary lift net fishermen was Rp. 9.284.424,- for each respondent. The factors of catches, operation durations and the locations of stationary lift net had a significant effect to the income of the stationary lift net fishermen.